Gender gaps in the performance of Norwegian biology students: the roles of test anxiety and science confidence - Sehoya Cotner; Lucas M. Jeno; J. D. Walker; Christian Jørgensen; Vigdis Vandvik (SpringerOpen, 2020)
Abstract Background Understanding student motivational factors such as test anxiety and science confidence is important for increasing retention in science, technology, engineering, and math (STEM), especially for underrepresented students, such as women. We investigated motivational metrics in over 400 introductory biology students in Norway, a country lauded for its gender equality. Specifically, we measured test anxiety and science confidence and combined students' survey responses with their performance in the class. Results We found that female students expressed more test anxiety than did their male counterparts, and the anxiety they experienced negatively predicted their performance in class. By contrast, the anxiety male students experienced did not predict their performance. Conversely, men had higher confidence than women, and confidence interacted with gender, so that the difference between its impact on men's and women's performance was marginally significant. Conclusions Our findings have implications for STEM instructors, in Norway and beyond: specifically, to counter gender-based performance gaps in STEM courses, minimize the effects of test anxiety.